Tinjauan Akad dalam Sistem Bainduk Samang di Huler Beras - Rolis, Robbi Etman; Arianti, Farida; Rahmi, Zikra (Fakultas Syariah IAIN Kediri, 2023)
This study examined the bainduk samang system in rice huler. The relationship between farmers and rice huler owners in accommodating rice/grain harvesting objects as trade objects. The purpose of how to bainduk samang that provides benefits in economic transactions such as capital, accounts receivable and accompanied by buying and selling between rice huller owners and farmers. Types of field research with descriptive qualitative methods. This research approach is with a phenomenological approach in the cold water community of Koto Tangah Padang. The results of this study show that the motives of farmers to do bainduk samang as a form of farmers' efforts for the sustainability of being able to grow crops. With the cooperation of Bainduk Samang to the owner of Huler. As a result, the contract is carried out with accounts receivable and buying and selling. The form of buying and selling is conditional, that is, it is to be sold to the lender at a price below the market. Conditional buying and selling in fiqh in order to reduce the price of the fasid buying and selling category